The Role of Alay Language in Online Relationship Dissolution: A Netnographic Study of TikTok Trend “Kenapa Gak Coba Sama Yang Baru?” - Lucia Winona Hahijary; Putra Sabiq (Metacommunication: Journal of Communication Studies, 2024)
The “Kenapa gak coba sama yang baru?” TikTok trend in Indonesia highlights the use of “typing jelek” in online relationship dissolution, in this case Alay language. This study aims to explore the motivations behind sharing private conversational failures on social media platforms, particularly within the context of the trend on TikTok. A netnographic content analysis of 28 TikTok posts following this trend reveals how Alay language can create negative first impressions in early stages of online relationships. The use of Alay language is now often perceived as outdated and can create a horn effect, negatively influencing overall perceptions of the sender, reflecting broader societal attitudes and cultural shifts in digital communication norms. The high engagement rates of posts featuring Alay language miscommunications suggest that this content resonates strongly with TikTok users, likely due to its relatability or entertainment value. Creators following this trend suggested were seeking validation and emotional support from others who have had similar experiences and engaging in a form of digital self-presentation. This study contributes to our understanding of how social media platforms can serve as spaces for shared experiences, even when those experiences are negative, potentially offering users a sense of community and validation through the sharing of communication mishaps.